New tariff regulation for natural monopolies: what should it be? - I. A. Dolmatov (Real Economics Publishing House, 2017)
For the last several years, the Russian Federation has been artificially restraining the growth of tariffs for the services of natural monopolies. A simple decision, which is taken hastily a few years ago as a short-term anti-crisis measure, has every chance of becoming a "solution" for many years to come. The authors attempt to analyze the short-term and long-term effects of the tariff regulation and present the results obtained in the framework of the basic research program of the Higher School of Economics on the impact of tariffs in the energy sector on the main macroeconomic indicators, most often used as arguments in favor of tariff restraint. It is shown that tariffs, including the ones for electricity networks, should cover all efficient costs of regulated companies in full which enables reliable and safe power supply for sustainable and efficient development of industries and wellbeing of the population. The authors present for the first time the results of the estimations of the efficiency of the operational costs of electric networks in Russia obtained on the models developed by the Institute of Pricing and Regulation of Natural Monopolies. The models are based on the data envelopment analysis (DEA) technique, one of the most advanced and most common methods in contemporary tariff setting.